2015
DOI: 10.1128/jvi.01009-14
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Lymphocytic Choriomeningitis Virus (LCMV) in Domestic Mice in Gabon: Risk of Emergence of LCMV Encephalitis in Central Africa

Abstract: e Lymphocytic choriomeningitis virus (LCMV) can cause acute fatal disease on all continents but was never detected in Africa. We report the first detection of LCMV RNA in a common European house mouse (Mus musculus domesticus) in Africa. Phylogenetic analyses show a close relationship with North American strains. These findings suggest that there is a risk of the appearance of LCMV acute encephalitis cases. This is a perfect example of virus dissemination by its natural host that may have dramatic public healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Thus, extensive sampling of LCMV sequences from different continents may reveal a different geographic origin for this virus. Notably, a recent search for LCMV in Gabon showed that the virus was introduced in the country, most likely with its rodent host, from America ( N’Dilimabaka et al. 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, extensive sampling of LCMV sequences from different continents may reveal a different geographic origin for this virus. Notably, a recent search for LCMV in Gabon showed that the virus was introduced in the country, most likely with its rodent host, from America ( N’Dilimabaka et al. 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…rattus [ 59 ]. Similarly, the Mus musculus domesticus specimens included in this study were genetically identified previously [ 53 ]. Lemniscomys striatus and Lophuromys sikapusi were identified to the species level by using morphological identification keys.…”
Section: Methodsmentioning
confidence: 99%
“…Many such pathogens may be carried by rodents, but in Gabon, very few studies have focused on inventories or the identification of potentially zoonotic infectious agents in these animals. The existing studies have focused on one virus at a time [ 52 , 53 ] and one plasmodium parasite [ 54 ] in rodents. They do not provide sufficient data to reveal the diversity and abundance of infectious agents carried by rodents in Gabon.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocytic choriomeningitis virus is widely distributed in America, Africa, Europe and Asia (Lavergne et al., ; Morita et al., ; N’ Dilimabaka et al., ). In China, only several cases have been reported in northeastern regions in recent 60 years, and seropositive wild house mice ( M. musculus ) have been found (Wei, ).…”
Section: Introductionmentioning
confidence: 99%